Konsep Lingkungan Bahasa Arab Informal Untuk Perguruan Tinggi - Muhammad Samin, Saproni; Zulkifli, Alfitri; Supriady, Harif (UIR Press, 2023)
Informal language learning outside the classroom plays an important and growing role in language learning and teaching. This research is qualitative research with a library research model. This study aims to determine the concept of an informal Arabic language environment for tertiary institutions and theoretical analysis of the substance to be measured, thus determining the conceptual definition. The steps taken in data collection refer to the actions specified by Thomas Mann with seven steps. The research data analysis uses 3 keywords; student autonomy, the era of disruption, and language communication. This study concludes that the Informal language environment has several characteristics and aspects. These elements, as well as aspects, are 1) Social and cultural contacts; 2) Virtual Learning and Website Proliferation; 3) support from teachers; 4) Learning language with Emotions is not just cognition; and 5) Institutional responsibility in the form of policies.